Integration of Corporate Social Responsibility and its Impact on The Triple Bottom Line: A Systematic Literature Review - Razy, Muh. Fachrul; Bahri, Nur Alim (West Science Accounting and Finance, 2025)
In recent years, the concept of Corporate Social Responsibility (CSR) has gained increasing importance as part of a company's sustainability strategy. CSR is not only about social or philanthropic activities, but also plays a role in improving a company's overall performance through the Triple Bottom Line (TBL) framework, which encompasses profit, people, and planet. This study conducted a systematic review of various studies that discussed the influence of CSR integration on a company's success in the economic, social, and environmental fields. Key findings indicate that successful CSR implementation is highly dependent on active stakeholder engagement, good corporate governance, and sustainability risk management. However, challenges remain in consistently aligning the three TBL aspects, particularly social and environmental aspects, which tend to be neglected for economic gain. This study emphasizes the need for close collaboration between companies, governments, and communities so that CSR can provide a sustainable positive impact for all parties involved.